2021
DOI: 10.24191/apmaj.v16i2-11
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Dividend Policy in Sri Lanka: The Panel Data Analysis

Abstract: The study aimed to emphasize the determinants of dividend policy in Sri Lankan firms. This study was conducted with 80 non - financial companies which were listed on Colombo Stock Exchange (CSE). The empirical research was focused on panel data analysis, and data was collected from annual reports for a five year period from 2013 to 2017. This study explored selected factors that influence dividend policy, including sales growth, leverage, firm size, profitability, EPS, liquidity, and risk. The panel data analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
5

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 32 publications
0
2
0
5
Order By: Relevance
“…They found that profitability and firm size are significant determinants and they both show a positive correlation with dividend policy. Kengatharan (2021) studied dividend policy determinants in Sri Lanka during the period 2013 to 2017. His research revealed that profitability, risk and earnings per share present a negative correlation with dividend policy.…”
Section: Empirical Results Of Previous Studies On the Determinants Of...mentioning
confidence: 99%
“…They found that profitability and firm size are significant determinants and they both show a positive correlation with dividend policy. Kengatharan (2021) studied dividend policy determinants in Sri Lanka during the period 2013 to 2017. His research revealed that profitability, risk and earnings per share present a negative correlation with dividend policy.…”
Section: Empirical Results Of Previous Studies On the Determinants Of...mentioning
confidence: 99%
“…Penelitian lainnya yang mendukung pernyataan tersebut yakni Martha & Juliani (2018), Putri et al, (2018), Fadillah & Eforis (2020), dan Manaf et al, (2021). Akan tetapi, terdapat bukti empiris lain yang menunjukkan hasil yang sebaliknya yakni profitabilitas justru memiliki pengaruh negatif terhadap kebijakan pembayaran dividen yakni penelitian oleh Yusuf & Rahmawati (2016), Ogundajo et al, (2019), dan Kengatharan (2021). Manaf et al, (2021) menguji aspek-aspek pemicu pembayaran dividen pada industri baja di Malaysia.…”
Section: Pendahuluanunclassified
“…Kebijakan pembayaran dividen harus didukung dengan ketersediaan aset lancar (kas) yang cukup guna pembayaran dividen tersebut. Pada penelitian Nehe et al, (2021), likuiditas memiliki pengaruh negatif dan pada beberapa penelitian lainnya justru memberikan pengaruh (Arsyad et al, 2021;Fadillah & Eforis, 2020;Herawati & Fauzia, 2018;Jackson & Laksmiwati, 2021;Kengatharan, 2021;Lie & Osesoga, 2020;Martha & Juliani, 2018;Rahmadi, 2020;Tahir & Mushtaq, 2016) Aspek lain pendorong kebijakan pembayaran dividen yakni rasio leverage. Tidak mudah bagi entitas dengan leverage yang tinggi untuk memutuskan apakah akan mendistribusikan dividen atau tidak kepada pemilik.…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…In addition, a better level of financial integrity also indicates that a government can achieve its economic policies, which accelerate the overall economic progress through better use of public funds (Combes et al,2019;Ortega, Sanjuán & Casquero, 2019). Moreover, governments' efficiency in domestic and international fund transactions can positively affect monetary activities, removing obstacles to fund leakage from the illicit leakage and helping in achieving economic goals (Bashi et al, 2022;Kengatharan, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%